Climb on! [book with audioplayer] - Paul, Baptiste ([Library Ideas, LLC], 2024)
"When a young child reminds her dad about the hike they planned, her father is hesitant --To the tippy top? It's a great day to watch futbol (soccer). But as the two climb on, her enthusiasm is contagious. Filled with setbacks, surprises, and stunning views, this warm and humorous story highlights in vivid colors the bonding power of a shared experience. A list of creatures at the end prompts a second look for keen-eyed readers to make discoveries of their own."--